Sustaining humanity through being fit to practice - Joy Chukwudolue, Ian Davies, Tahmina Hussain (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The Health & Care Professions Council, who regulate biomedical scientists and other professions, defines fitness to practice as having the knowledge, skills, health, and character to practice your profession safely and effectively2. Being fit to practice equips a Biomedical scientist with the skills and knowledge needed to perform a task safely and effectively in the laboratory. To understand fitness to practice better, I spoke with Tahmina Hussain and Ian Davies who collectively have decades of experience working as biomedical scientists. Mrs Tahmina Hussain has a background as a biomedical scientist, and a pathology training coordinator, and is currently a university lecturer. Mr Ian Davies has over 20 years of experience working as a biomedical scientist, progressing to a senior Biomedical scientist role and then to a laboratory manager. Currently, he works as a university lecturer at Staffordshire University and a panel member for the Health & Care Professions Council (HCPC) fitness to practice hearings.